Development of Traditional Markets to Increase Visitor Interest in the Mayong Traditional Market, Kec. Mayong District. Jepara - Darsin (Indonesian Journal of Advanced Research, 2023)
Traditional markets are market locations where sellers and buyers can meet each other so that buying and selling transactions occur. The advantage of the market is the availability of all kinds of goods at affordable prices for the community. For this reason, market services must be considered so that visitors feel satisfied. So that innovation is needed to make visitors satisfied by improving the physical, environmental, administration to market order. There are several factors that support traditional market innovation, namely from related agencies such as the industry and trade services, parking attendants, traders and market managers. In addition to supporting factors, there are also inhibiting factors such as littering, illegal parking, damaged floors and odors. In this study, the approach taken was qualitatively regarding the description of traditional market innovations in Mayong Jepara in order to attract visitors.